Stravinsky : His Thoughts and Music - Jarzębska, Alicja (Bern Peter Lang International Academic Publishing Group, 2020)
This book is an attempt at a new interpretation of Stravinsky s thoughts about music and art, an interpretation made in dialogue with the philosophy of new music and 19th-century artistic ideas. It is also a proposal for a new method of analysing the construction of his musical masterpieces (for example a proposal of new formal sound-units: partons with perceptual invariance), a method in-spired by research into cognitive psychology. Furthermore, in the analysis of Stravinsky s music, the author emphasises its connection with the Eastern and Western traditions of European culture and links with Plato s triad of values.
English
Keywords: Theory of music & musicology; History: specific events & topics; history of music; Jarzebska; Music; music analysis; musical aesthetics; musical psychology; new music; serial music; Stravinski; Stravinsky; Thoughts